Don't Blame the Messenger: A Field Experiment on Delivery Methods for Increasing Tax Compliance - Daniel Ortega; Carlos Scartascini (Inter-American Development Bank (IDB), 2015)
There is an ample literature on the determinants of tax compliance. Several field experiments have evaluated the effect and comparative relevance of sending deterrence and moral suasion messages to taxpayers. The effect of different delivery mechanisms, however, has not been evaluated so far. This study conducts a field experiment in Colombia that varies the way the National Tax Agency contacts taxpayers on payments due for income, value added, and wealth taxes. More than 20,000 taxpayers were randomly assigned to a control or one of three delivery mechanisms (letter, email, and personal visit by a tax inspector). Results indicate large and highly significant effects, as well as sizable differences across delivery methods. A personal visit by a tax inspector is more effective than a physical letter or an email, conditional on delivery, but email tends to reach its target more often. Improving the quality of taxpayer contact information can significantly improve the collection of delinquencies.
hdl:11319/7284
Keywords: C93; D03; H26; 330; Tax compliance; Field experiments; Delivery methods; Optimal enforcement strategies; Public policy